A people's revolt in Travancore : a backward class movement for social freedom - Yesudas, R. N. (Kerala Historical Society : copies can be had from M. J. Koshy, 1975)
Account of the movement led by the Nadars (formerly known as Shanars) against the caste Hindus in the early 19th century to secure social justice for underprivileged communities.